Educational software for power system analysis - (:unkn) unknown (MANCHESTER UNIV PRESS, 2014)
This paper presents educational software that has an unconventional structure and friendly interface and can be used in computer-aided analysis of power systems. The software provides effective and fast solutions to in-line modeling of power systems, failure and power flow analyses. In addition, students using this software can demonstrate their own models and follow the solution steps in detail. The software also presents educational details and graphical mediums, similar to solutions provided by software developed for professional use. For this reason, it has a form that can be used in a workshop environment and distance learning activities.
Keywords: distance education; educational software; power flow; power system analysis; GRAPHIC PACKAGE; ENVIRONMENT; OPERATION